Advances in environmental remote sensing : sensors, algorithms, and applications - Weng, Qihao (Taylor & Francis series in remote sensing applications series, 2011)
"1. Aims and Scope The main purpose of compiling such a book is to provide an authoritative supplementary text for upper division undergraduate and graduate students, who may have chosen a text book from a variety of choice in the market. This book collects two types of articles: (1) comprehensive review articles from leading authorities to examine the developments in concepts, methods, techniques, and applications in a sub-field of environmental remote sensing; and (2) focused review articles in respect of the latest developments in a hot topic area with one to two concise case studies. Because of the nature of articles collected, this book can also serve as a good reference book for researchers, scientists, engineers, and policy-makers who wish to keep up with new developments in environmental remote sensing"--Provided by publisher